Risk, uncertainty and opportunity in climate change coverage: Australia compared - Lyn McGaurr; Elizabeth Lester; Painter, J (2013)
Mediation of climate change is bedevilled by the complexity of communicating scientific uncertainty. This paper revisits the results of a recent comparative study using frame analysis to investigate newspaper coverage across six countries of scientific reports from the Intergovernmental Panel on Climate Change and articles about changes in Arctic sea ice. Our paper looks more closely at what these comparative data tell us is distinctive about the mediation of climate science in Australia, namely that the Australian newspapers analysed were most likely to include sceptical voices, least likely to include an opportunity frame and less likely than most to temper uncertainty frames with references to increasing certainty. We discuss these findings in the context of political argument in Australia about the merits or otherwise of trading or taxing greenhouse gas emissions.